Back analysis of two collapses in underground coal mines : cases of coalbrokok (South Africa) and Gardanne (France) - (:unkn) unknown (My University, 2010)
The paper proposes the back analysis of two major accidents that have occurred within underground coal mines. The first one concerns the Coalbrook disaster, in South-Africa, that killed more than 400 miners. The second one deals with the collapse of a whole sector of a mine located in the Provence coal basin (SE of France). This one did not induce any victim but generated major damage for the exploitation. After a description of the contexts of the two mines as well as the manifestation of the collapses, the paper presents the major improvements in the field of rock mechanics, which resulted from the analysis of both events. In the case of Coalbrook, the researches were mainly devoted to a better characterisation of the in situ pillar strength. In the case of the Provence coal field, the development performed made it possible to analyse, with the help of numerical modelling, the mechanism 'crushing pillars - brittle roof' identify at the origin of two brutal collapses. Some perspectives and identification future developments are finally proposed.
Keywords: African Research